2018
DOI: 10.1002/jcb.27661
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potency of oncolytic virotherapy–induced cancer stem cells targeting in brain tumors, current status, and perspectives

Abstract: Brain tumors are the most common form of solid tumors in children and is presently a serious therapeutic challenge worldwide. Traditional treatment with chemotherapy and radiotherapy was shown to be unsuccessful in targeting brain tumor cancer stem cells (CSCs), leading to recurrent, treatment-resistant secondary malignancies. Oncolytic virotherapy (OV) is an effective antitumor therapeutic strategy which offers a novel, targeted approach for eradicating pediatric brain tumor CSCs by utilizing mechanisms of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…OVs can directly infect and eliminate tumor cells by identifying special biomarkers that are overexpressed on cancer cells like laminin and CD64 or causing immune attack via cytolytic cells indirectly, or both ways together 189,192 (Figure 1). Current data have shown OVs' ability in targeting CSCs in different types of cancers including brain tumors 193 . Accordingly, Gp73‐regulated oncolytic AD exhibited toxic effects on hepatic CSCs and induced apoptosis in vitro and in vivo 194 .…”
Section: Novel Immune‐based Therapeutic Modalities Against Cscsmentioning
confidence: 99%
“…OVs can directly infect and eliminate tumor cells by identifying special biomarkers that are overexpressed on cancer cells like laminin and CD64 or causing immune attack via cytolytic cells indirectly, or both ways together 189,192 (Figure 1). Current data have shown OVs' ability in targeting CSCs in different types of cancers including brain tumors 193 . Accordingly, Gp73‐regulated oncolytic AD exhibited toxic effects on hepatic CSCs and induced apoptosis in vitro and in vivo 194 .…”
Section: Novel Immune‐based Therapeutic Modalities Against Cscsmentioning
confidence: 99%
“…In cellular and animal experiments, they demonstrated that MYXV destroyed BTIC and increased the survival of BTIC-bearing mice. Furthermore, even in mice with “advanced” BTIC tumors, the combination of MYXV and rapamycin significantly improved MYXV’s antitumor activities [ 98 ]. Akt signaling is essential for cell growth, proliferation, and survival.…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
“…DNX-2401 will be given intratumorally at a dosage of 1.0 mL into the brain tumor as part of this trial. Patients will have intravenous pembrolizumab, 200 mg every 3 weeks for 105 weeks (2 years), after 7 to 9 days (NCT02798406) [ 98 , 109 ]. To encourage selective replication in tumor cells and reduce viral toxicity, the most common change is deleting non-essential viral genes.…”
Section: Genetic Engineering Of Oncolytic Virusesmentioning
confidence: 99%
“…Targeting CSC by OVs has emerged as a novel and effective strategy for glioma treatment to achieve long-term control. OVs are capable of destructing cancer cells as well as CSC in preclinical data [ 59 ]. Fast-track approval of several OVs (DNX-2401, Toca511, and PVS-RIPO) by the FDA were granted for brain tumors, after they showed durable complete responses in about 20% of patients and rare serious side effects [ 60 ].…”
Section: Oncolytic Virus Therapymentioning
confidence: 99%